Relative age effect in international ski jumping: analysis of FIS World Cup and FIS Junior World Ski Championships - Hammer, T. (Journal of Physical Education and Sport, 2020)
The aim of the current investigation was to examine whether the relative age effect was present within the elitelevel category of international ski jumping and, for the first, time asses the relative age effect at the junior level of international ski jumping. Male and female athletes who placed among the top fifty in the overall World Cup rankings from 1999 to 2019 and the top fifty male and female athletes in the Junior World Championships each year between 2009 and 2019 were selected for analysis. The birthdates of senior (n = 409) and junior (n = 507) athletes were collected from open access websites and analyzed by chi-square statistics to determine the occurrence of relative age effect in juniors and seniors and by sex. When compared with the actual live birth distributions from the European Union and Japan, the distribution of ski jumpers birthdates does not show any statistically significant relative age effect for either sex at any level. The results show that being relatively older than competitors does not drive performance development in elite ski jumping. The primary performance characteristic in ski jumping is technique rather than physical strength, and this is suggested as the foremost explanation for the lack of any significant relative age effect in international ski jumping. Furthermore, low body weight is a performance advantage in this sport; thus, it is not an advantage to be physically larger than opponents. These results show that the relative age effect in competitive sports is affected by the typical performance characteristics of a given activity.